2022
DOI: 10.1111/1440-1681.13668
|View full text |Cite
|
Sign up to set email alerts
|

Expression of anti and pro‐inflammatory genes in human endothelial cells activated by 25‐hydroxycholesterol: A comparison of rivaroxaban and dabigatran

Abstract: Atherosclerosis is associated with a haemostatic imbalance characterized by excessive activation of pro‐inflammatory and pro‐coagulant pathways. Non‐vitamin K antagonists oral anticoagulant (NOACs) may reduce the incidence of cardiovascular events, cerebral ischemia, thromboembolic events and atherosclerosis. Chronic inflammation, vascular proliferation and the development of atherosclerosis is also influenced by 25‐hydroxycholesterol (25‐OHC). The aim of the study was to assess the effect of rivaroxaban and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Following the examples of statins, metformin, and several other widely used cardiovascular drugs, a search for additional (pleiotropic) effects is currently underway in several preclinical and clinical studies. As it collectively derives from the studies reviewed herein, DOACs have several pleiotropic actions in ECs; it appears that apart from anticoagulation, they exert several additional beneficial actions on the endothelium (depicted in Figure 2 ), including anti-oxidant ( Torramade-Moix et al, 2021 ), anti-inflammatory ( Álvarez et al, 2018 ), atheroprotective ( Gorzelak-Pabiś et al, 2022b ), anti-senescence ( Sanada et al, 2016 ), and anti-fibrotic effects ( Imano et al, 2021 ). Moreover, they preserve endothelial integrity ( Benelhaj et al, 2019 ; Gorzelak-Pabiś et al, 2022a ; Zolotoff et al, 2022 ) and reduce thrombogenicity ( Torramade-Moix et al, 2021 ).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Following the examples of statins, metformin, and several other widely used cardiovascular drugs, a search for additional (pleiotropic) effects is currently underway in several preclinical and clinical studies. As it collectively derives from the studies reviewed herein, DOACs have several pleiotropic actions in ECs; it appears that apart from anticoagulation, they exert several additional beneficial actions on the endothelium (depicted in Figure 2 ), including anti-oxidant ( Torramade-Moix et al, 2021 ), anti-inflammatory ( Álvarez et al, 2018 ), atheroprotective ( Gorzelak-Pabiś et al, 2022b ), anti-senescence ( Sanada et al, 2016 ), and anti-fibrotic effects ( Imano et al, 2021 ). Moreover, they preserve endothelial integrity ( Benelhaj et al, 2019 ; Gorzelak-Pabiś et al, 2022a ; Zolotoff et al, 2022 ) and reduce thrombogenicity ( Torramade-Moix et al, 2021 ).…”
Section: Discussionmentioning
confidence: 91%
“… Gorzelak-Pabiś et al (2022b) also evaluated the effects of the same DOACs in a HUVECs inflammation model. Stimulation of HUVECs with 25-OHC caused downregulation of transforming growth factor beta 1 ( TGFB1 ) and IL-37, and upregulation of IL-18, IL-23, and IL-35, which were counterbalanced when ECs were pre-incubated with rivaroxaban or dabigatran.…”
Section: In Vitro Experiments Using Doacs On Ecsmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, preclinical studies showed anti-inflammatory, antioxidant and anti-fibrotic effects on endothelial cells. Importantly, several studies highlighted DOAC-mediated effects on endothelial cells in terms of improvement in endothelial function and integrity and the inhibition of neo-angiogenesis [ 22 , 39 , 40 ]. Although peculiar effects of a single molecule have not yet been determined, it is generally accepted that factor Xa inhibitors produce anti-angiogenic and anti-fibrotic effects beyond the anti-inflammatory action and stabilization of endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Forearm blood flow was also improved in diabetic patients administered rivaroxaban for 20 weeks, although treatment was associated with higher bleeding events ( 150 ). In vitro , rivaroxaban reduced ROS (reactive oxygen species), improved DNA repair ( 151 ) and reduced inflammatory gene expression in ECs exposed to hydroxycholesterol ( 152 , 153 ). Rivaroxaban also stimulated blood flow and increased capillary density in a mouse model of diabetic PAD ( 154 ).…”
Section: Current Treatments and Clinical Trials Which Target And Impr...mentioning
confidence: 99%